Integration of Scientific Competence into Gross Anatomy Teaching Using Poster Presentations: Feasibility and Perception among Medical Students. Issue 1 (18th February 2021) - Schön, Michael; Steinestel, Konrad; Spiegelburg, Doreen; Risch, Annika; Seidel, Mira; Schurr, Leon; Fassnacht, Ulrich Kai; Golenhofen, Nikola; Böckers, Tobias Maria; Böckers, Anja
Abstract : Scientific competencies, as defined in the German competency framework, describe the ability to think independently and act scientifically which is a central component of medical education. This report describes integration of scientific competencies into anatomical teaching. Based on findings seen in two consecutive years of dissection courses, students worked on either a case report (n = 70) or an original research study (n = 6) in the format of a scientific poster while learning to use primary literature. Posters were evaluated by juror teams using standardized evaluation criteria. Student perception of the project was assessed by quantitative and qualitative data obtained from the faculty's course evaluation and an online‐survey. Overall, students worked collaboratively and invested extra‐time (median 3.0 hours) in poster creation. Primary literature was integrated in 90.8% of the posters. Overall poster quality was satisfactory (46.3 ± 8.5 [mean ± standard deviation] out of 72 points), but several insufficiencies were identified. Students integrated information gained from the donor's death certificate, post‐mortem full‐body computed tomography (CT) scan (22.4%), and histopathological workup (31.6%) in their case reports. Students responded positively about learning new scientific skills (median 4.0 on a six‐point Likert scale), but free‐text answers revealed that some students experienced the project as an extra burden in a demanding gross anatomy course. In summary, it was feasible to introduce students to scientific skills during the dissection course and to increase interest in science in approximately a third of the survey respondents. Further adjustments to ensure the posters' scientific quality might be necessary for the future.